Knowledge, attitudes and practices on child feeding among child care providers of preschools in a nutritionally vulnerable district in Sri Lanka - Hemali G. Jayakody; Deepika E. Attygalle (College of Community Physicians of Sri Lanka, 2016)
Background Role of child care providers in changing eating habits and food consumption among preschool children is often highlighted. Objectives This study described knowledge, attitudes and practices on child feeding and factors associated with knowledge and attitudes among child care providers of preschools in Nuwaraeliya district. Methods Cross sectional descriptive study was conducted in three divisional secretariat areas in Nuwaraeliya district in a sample of 427 preschool teachers who are working in child care centres for more than 1 year. Results Response rate for the self-administered questionnaire was 82.1% (n=344). Mean total knowledge score was 5.49 (SD 1.9) and 52.6% (n=181) scored more than 50% of the total score. Positive attitudes toward child feeding were reported as 63.7% (n=219). Statistically significant associations for both knowledge score and attitude level were observed with ethnicity (p=0.001), level of education (p=0.001), minimal duration of basic training (p=0.008 and p=0.001), type of in-service nutrition training programme attended (p=0.0001 and p=0.009) and the sector of employment of the child care provider (p=0.0001 and p=0.003). Participation of care providers during feeding of children was 83.3% (n= 283). Almost 59% (n=223) incorporated nutrition messages into routine teaching. Conclusion Standard basic training and well organized in-service training are some of the modifiable factors in improving the knowledge and attitudes on child feeding among preschool teachers.